2007
DOI: 10.2174/157488907779561763
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Targets for the Prevention of Fetal Alcohol Syndrome

Abstract: Alcohol abuse produces damaging effects on the CNS that leads to several types of disorders. When consumed during pregnancy, alcohol may cause craniofacial malformations, growth retardation and brain damage in offspring. These symptoms are grouped by the term fetal alcohol syndrome (FAS). FAS is the most common cause of non-genetic mental retardation in the western world. Substantial efforts to elucidate the molecular basis of these impairments are currently in progress. Whereas FAS is totally preventable by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 207 publications
(255 reference statements)
0
14
0
Order By: Relevance
“…Thus, there is extensive evidence to support that alcohol affects a variety of cellular processes in the developing brain through different molecular mechanisms [13,14]. Among these mechanisms, ethanol has been proposed to perturb protein trafficking, including protein glycosylation, exocytosis and endocytosis [14,15-20]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is extensive evidence to support that alcohol affects a variety of cellular processes in the developing brain through different molecular mechanisms [13,14]. Among these mechanisms, ethanol has been proposed to perturb protein trafficking, including protein glycosylation, exocytosis and endocytosis [14,15-20]. …”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous mechanisms that have been proposed for ethanol (EtOH)-induced teratogenesis, the premise that EtOH alters normal development via disruption of reactive oxygen species (ROS) homeostasis has received considerable research attention and support (Henderson et al, 1999; Martinez and Egea, 2007). In this regard, a number of experimental studies have shown that oxidative stress-induced apoptosis of selected cell populations results from EtOH exposure in embryos, with the induced cell death pattern being predictive of the subsequent defects (Chen and Sulik, 1996; Davis et al, 1990; Heaton et al, 2000; Kotch et al, 1995; Spong et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional supplementation may also mitigate alcohol's teratogenic effects. Nutritional supplements may compensate for changes in the bioavailability of Extracted from Martinez and Egea (2007). nutrients due to alcohol metabolism (Lieber, 2000).…”
Section: Discussionmentioning
confidence: 99%